2019
DOI: 10.1016/j.jid.2018.11.033
|View full text |Cite
|
Sign up to set email alerts
|

WAKMAR2, a Long Noncoding RNA Downregulated in Human Chronic Wounds, Modulates Keratinocyte Motility and Production of Inflammatory Chemokines

Abstract: Chronic wounds represent a major and growing health and economic burden worldwide. A better understanding of molecular mechanisms of normal as well as impaired wound healing is needed to develop effective treatment. Herein we studied the potential role of long noncoding RNA LOC100130476 in skin wound repair. LOC100130476 is an RNA polymerase IIeencoded polyadenylated transcript present in both cytoplasm and nucleus. We found that its expression was lower in wound-edge keratinocytes of human chronic wounds comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 62 publications
2
48
0
Order By: Relevance
“…According to our screening criteria, WAKMAR2 was selected to enter the follow-up study. The original name of WAKMAR2 is LOC100130476, its genomic locus is very special, its transcription direction is antisense, and there is an overlapping region with the TNFAIP3 gene body and promoter part [20,21]. The expression of WAKMAR2 and TNFAIP3 has a strong correlation in various tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…According to our screening criteria, WAKMAR2 was selected to enter the follow-up study. The original name of WAKMAR2 is LOC100130476, its genomic locus is very special, its transcription direction is antisense, and there is an overlapping region with the TNFAIP3 gene body and promoter part [20,21]. The expression of WAKMAR2 and TNFAIP3 has a strong correlation in various tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…15 Full keratinocyte coverage (i.e., epithelization) is the defining clinical criteria of a closed wound. 16 Li et al identified novel roles for two lncRNAs-LOC105372576 (renamed WAKMAR1 [wound and keratinocyte migration-associated lncRNA 1]), 17 and LOC100130476 (renamed (WAKMAR2 [wound and keratinocyte migration-associated lncRNA 2]) 18 -that both increase keratinocyte migration in wound F I G U R E 1 Role of long noncoding RNA (lncRNA) in endothelial cell (EV)-derived bioactivity. (a) Expression levels of the indicated lncRNAs were assessed by qPCR in EVs from human umbilical vein endothelial cells (HUVECs) cultured in the presence versus absence of 100 mM ethanol (EtOH) for 24 hr (n = 3; *p < .05).…”
Section: Integumentary Systemmentioning
confidence: 99%
“…Wound and keratinocyte migration-associated lncRNA 1 and 2 (WAKMAR1 and WAKMAR2) are two recently identified lncRNAs, which play an important role in cutaneous wound repair [90,91]. Expression of WAKMAR1 is highly upregulated in keratinocytes during wound repair and its expression stimulates keratinocyte migration and wound re-epithelization [90].…”
Section: Deregulation Of Lncrnas Is Becoming Evident In Cscc Progressmentioning
confidence: 99%
“…Expression of WAKMAR1 is highly upregulated in keratinocytes during wound repair and its expression stimulates keratinocyte migration and wound re-epithelization [90]. Expression of both WAKMAR1 and WAKMAR2 is induced by TGF-β and downregulation of their expression inhibits migration of keratinocytes, resulting in delayed wound re-epithelization [90,91]. Accordingly, the expression of both WAKMAR1 and WAKMAR2 is reduced in keratinocytes in the edge of chronic wounds in vivo [90,91].…”
Section: Deregulation Of Lncrnas Is Becoming Evident In Cscc Progressmentioning
confidence: 99%
See 1 more Smart Citation